THE EFFECT OF EXECUTIVE COMPENSATION, PROFITABILITY, LEVERAGE, CAPITAL INTENSITY AND COMPANY AGE ON TAX AVOIDANCE - Darmanto; Oktavianus Satu (Media Akuntansi, 2021)
profitability, leverage, capital intensity and age against tax avoidance. Population in this reasearch is the company LQ45 index in Indonesia Stock Exchange period 2017-2020. The method of determining the sample used in this reasearch was purposive sampling. Total sample used in this reasearch is 120 financial report from 30 company. The Hypothesis in this research was tested using multiple regresion analysis. The results of the study found 1) executive compensation had a significant positive effect on tax avoidance (p = 0.000), 2) profitability had no significant effect on tax avoidance (p = 0.533), 3) leverage had no significant effect on tax avoidance (p = 0.341), 4 ) capital intensity has a significant positive effect on tax avoidance (p = 0.001), 5) company age has no significant effect on tax avoidance (p  = 0.846).